Kobiety z warstwy rycerskiej w dokumentach wielkopolskich z okresu rozbicia dzielnicowego - Teterycz-Puzio, Agnieszka (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2024)
In the paper, a question is posed about the legal status of knighthood women in Wielkopolska during the country’s fragmentation from the 12th century to the early 14th century. The conclusions have been drawn on the basis of documents written in Wielkopolska and in the lands governed by the dukes nof the Wielkopolska line of the Piast dynasty, documents issued by the rulers of Wielkopolska or diplomas concerning people connected with Wielkopolska through offices or estates. Sixty-nine documents have been analysed. Most often, women are referred to in the body of the document (in the disposition), nrarely in the intitulation (in two cases they appeared as co-authors of documents), and in the testation only as an exception. There are several types of documents in which women are referred. From the documents we learn that women disposed of their property. Estates could be a part of a woman’s marriage settlement; widows also made donations to pass on their daughters’ dowries. Knights also secured the fortunes of their wives, daughters, and mothers by document, especially through endowments to monasteries. Women were given a certain amount of property for life but were also placed under the protection of the Church. Quite a number of documents mention the salvation of the soul of the donor and his wife. The analysed documents from the 12th to the beginning of the 14th century include diplomas regulating family situations, i.e. not issued for ecclesiastical institutions, although the latter are nevertheless predominant. In the light of the documents analysed, various issues concerning the fate of women are also apparent, e.g. the situation of women following their husbands in the 13th century, or their status after the execution of their husbands. Compared to the neighbouring districts of Mazovia and Krakow and Sandomierz Principalities, Wielkopolska boasts a larger number of documents with mentions of women. An analysis of the documents indicates that women’s rights to property and the possibility of disposing of it were recognised in Wielkopolska, although the confirmations of dukes (issued frequently) may suggest that the dispositions made by women were questioned.